Proportionate methods for evaluating a simple digital mental health tool - Davies, Eleanor Bethan; Craven, Michael P.; Martin, Jennifer L.; Simons, Lucy (BMJ Publishing Group, 2017)
Background: Traditional evaluation methods are not keeping pace with rapid developments in mobile health. More flexible methodologies are needed to evaluate mHealth technologies, particularly simple, self-help tools. One approach is to combine a variety of methods and data to build a comprehensive picture of how a technology is used and its impact on users.